Early identification of risk factors and diagnosis of metabolic syndrome in overweight and obese children above 6 years of age - B., Minakshi; N. S., Chithambaram (International Journal of Contemporary Pediatrics, 2017)
Background: Metabolic syndrome is a complex disorder and an emerging clinical challenge all over the world. It is considered a multiplex cardiovascular risk factor, in that each component of the cluster of abnormalities is a risk factor in its own right. The objective of the study was to identify the risk factors and diagnose metabolic syndrome early in overweight and obese children. Methods: The observational study was conducted at the Vydehi Institute of Medical Sciences and Research Centre, Bangalore. Total 100 children who were overweight and obese were participated. The outcome measure of the study was considered as metabolic syndrome. In patients above 6 years who are overweight and obese, a detailed history including antenatal history, birth weight, diet history, personal history was taken. In these patient’s demographic details, anthropometric measurements weight, height, BMI, waist circumference, waist hip ratio and blood pressure were recorded. FBS, triglyceride and HDL were also done. Results: Out of 100 children studied, 61% were overweight and 39% were obese. Males were 52% and females were 48%. 92 were AGA, 6 were SGA and 2 were LGA .92% had normal FBS and 8% had high levels of FBS .85% had normal TGL and 15% more than 150mg/dl. 69% had HDL-C less than 40 mg/dl and 31% had HDL-C more than or equal to 40mg/dl. Out of 8 cases of MS, 3 had abnormal FBS and HDL-C, 2 cases had abnormal TGL and HDL-C, and 3 cases abnormal FBS, TGL and HDL-C. In the remaining 92 cases, only one metabolic abnormality was noticed in 73 cases (abnormal FBS- 2, abnormal TGL-10 and abnormal HDL-C in 61) and in remaining 19 cases none of the risk factors for MS were detected. Conclusions: By identifying these risk factors early in overweight and obese children, we can identify metabolic syndrome early and initiate necessary treatment and prevent the complications of MS.